New species and records of subgenus Aethina from China (Coleoptera: Nitidulidae) - Chen, Xiaoxiao; Zhang, Jianhui; Huang, Min (Zootaxa, 2024)
Two new species of sap beetles, A. (A.) similinconspicua sp. nov. and A. (A.) shizhuica sp. nov., of the subgenus Aethina Erichson, 1843 are described and illustrated from southwestern China. And four new species, A. (A.) cyaneipennis Grouvelle, 1903, A. (A.) dubitabilis Kireitshuk, 1986, A. (A.) kirejtshuki Jelínek, 1995, and A. (A.) lindskogi Jelínek & Kirejtshuk, 1986 are recorded for the first time from China.